PENGARUH KUALITAS PRODUK, KEMASAN DAN CITA RASA TERHADAP MINAT BELI KONSUMEN PADA PRODUK STIK UBI DI KELURAHAN TANGSI BARU KABAWETAN KABUPATEN KEPAHYANG - Syahputra, Reza Agung; Sismanto, Adi (UM. Bengkulu, 2024)
Research on Sweet Potato Sticksin Tangsi Baru Village, Kabawetan, Kepahyang Regency witha problem formulation Howis Product Quality, Packaging and Tasteon Consumer Buying Interestin Sweet Potato Sticksin Tangsi Baru Village, Kabawetan, Kepahyang Regency? And The purpose of this study is tofin dout how thein fluenceof Product Quality, Packaging and Tasteon Consumer Buying Interestin Sweet Potato Sticksin Tangsi Baru Village, Kabawetan, Kepahyang Regency The population use din this study is allemploye eswho workon Sweet Potato Sticksin Tangsi Baru Village, Kabawetan, Kepah Regency, totaling143 respondents.Thesampling techni queuses total sampling based on creteria that has been determined tobe143 respondents. Product Quality (X1) positive influence on consumer buying interest (Y) consumers of Sweet Potato Stick Products in Tangsi Baru Village, Kabawetan, Kepahyang Regency,. Packaging (X2) positive influence on consumer buying interest(Y) consumers of Sweet Potato Stick Products in Tangsi Baru Village, Kabawetan, Kepahyang Regency. Taste (X2) positive influence on consumer buying interest (Y) consumers of SweetPotato Stick Productsin TangsiBaru Village, Kabawetan, Kepahyang Regency, Product Quality (X1), Packaging (X2), and Taste (X3) influence on consumer buying interest (Y). Keywords : Product Quality (X1), and Packaging (X2) to Consumer buying interes